Chronic In Vivo Load Alteration Induces Degenerative Changes in the Rat Tibiofemoral Joint - Roemhildt, M. L. (2012)
OBJECTIVE: We investigated the relationship between the magnitude and duration of sustained compressive load alteration and the development of degenerative changes in the rat tibiofemoral joint. METHODS: A varus loading device was attached to the left hind limb of mature rats to apply increased compression to the medial compartment and decreased compression to the lateral compartment of the tibiofemoral joint of either 0% or 100% body weight for 0, 6 or 20 weeks. Compartment-specific assessment of the tibial plateaus included biomechanical measures (articular cartilage aggregate modulus, permeability and Poisson’s ratio, and subchondral bone modulus) and histological assessments (articular cartilage, calcified cartilage, and subchondral bone thicknesses, degenerative scoring parameters, and articular cartilage cellularity). RESULTS: Increased compression in the medial compartment produced significant degenerative changes consistent with the development of osteoarthritis including a progressive decrease in cartilage aggregate modulus (43% and 77% at 6 and 20 weeks), diminished cellularity (38% and 51% at 6 and 20 weeks), and increased histological degeneration. At 20 weeks, medial compartment articular cartilage thickness deceased 30% while subchondral bone thickness increased 32% and subchondral bone modulus increased 99%. Decreased compression in the lateral compartment increased calcified cartilage thickness, diminished region-specific subchondral bone thickness and revealed trends for reduced cellularity and decreased articular cartilage thickness at 20 weeks. CONCLUSIONS: Altered chronic joint loading produced degenerative changes consistent with those observed clinically with the development of osteoarthritis and may replicate the slow development of non-traumatic osteoarthritis in which mechanical loads play a primary etiological role.